Fine Particulate Matter Triggers α‐Synuclein Fibrillization and Parkinson‐like Neurodegeneration. Issue 9 (22nd August 2022) - Yuan, Xin; Yang, Yingxu; Liu, Chaoyang; Tian, Ye; Xia, Danhao; Liu, Zehua; Pan, Lina; Xiong, Min; Xiong, Jing; Meng, Lanxia; Zhang, Zhaohui; Ye, Keqiang; et al.
ABSTRACT: Background: The deposition of α‐synuclein (α‐Syn) in the brain is the pathological hallmark of Parkinson's disease (PD). Epidemiological data indicate that exposure to fine particulate matter (≤2.5 μm in aerodynamic diameter [PM2.5]) is associated with an increased risk for PD. Objective: The aim of this study is to investigate whether PM2.5 has a direct effect on α‐Syn pathology and how it drives the risk for PD. Methods: PM2.5 was added into α‐Syn monomers and different cell models to test whether PM2.5 can promote the fibrillization and aggregation of α‐Syn. α‐Syn A53T transgenic mice and α‐Syn knockout mice were used to investigate the effects of PM2.5 on PD‐like pathology. Results: PM2.5 triggers the fibrillization of α‐Syn and promotes the formation of α‐Syn fibrils with enhanced seeding activity and neurotoxicity. PM2.5 also induces mitochondrial dysfunction and oxidative stress. Intrastriatal injection or intranasal administration of PM2.5 exacerbates α‐Syn pathology and dopaminergic neuronal degeneration in α‐Syn A53T transgenic mice. The detrimental effect of PM2.5 was attenuated in α‐Syn knockout mice. Conclusions: Our results identify that PM2.5 exposure could promote the α‐Syn pathology, providing mechanistic insights into how PM2.5 increases the risk for PD. © 2022 International Parkinson and Movement Disorder Society. Abstract : September Infographic: Fine Particulate Matter Triggers α‐Synuclein Fibrillization and Parkinson‐like Neurodegeneration